LAPORAN AKUNTABILITAS KINERJA DINAS PENDIDIKAN KOTA SURABAYA MELALUI PENDEKATAN VALUE FOR MONEY - Subastian, Avib (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out the presentation of government agency performance accountability (gapa) report based on government regulation number 8 year 2006at Department of Education in the city ofSurabaya.The concept of value for money in the preparation of government agency performance accountabilityreport is intended to explain that the performance assessment is based on three aspects of assessment that areeconomical aspect, aspect of efficiency, aspect of effectiveness. The criteria which is used to assess the success inachieving agency goals is embodied in three performance indicators: input indicator, output indicator, andoutcome indicator. The analysis results and the discussion show that performance accountability report is basedon the concept of value for money at the agency in 2011 is presented in appropriate with the guideline of gapareport. Agency performance, in general, has run well, yet there is program implementation result which has notbeen achieved optimally. Performance assessment in achieving the program goal can be said successful. It can beseen from economic performance which considers input value based on the market price while the efficientperformance can be seen from the output realization which has been generated to the inputs, namely the budget.Meanwhile, the effective performance can be seen from the output and outcome. Output and outcome indicatorsshould be developed by considering its relevancy with its program objectives and activities for the qualityimprovement of agency performance reporting in the future.Keywords: Government Agency Performance Accountability, Value for Money, Economics, Efficient, Effectiveness